Indutores de resistência e seus efeitos sobre Bipolaris sorokiniana e Azospirillum brasilense em trigo: custos adaptativos e ecológico - Iurkiv, Luciana (2016)
The induced resistance efficiency in the control of pathogens is recognized, however there are costs related to its use that are still little researched, as the case of fitness and ecological costs. This research aims to verify the efficiency of use of the acibenzolar-S-methyl (ASM), mannanoligosaccharide (MOS) and B. cereus inductors in the control of spot blotch wheat disease, and its relation with the induction of enzymes related to the plant defense, as well as the interference on gas exchanges, on the non-target microrganisms A. brasilense, and on the crop production. The experiment was conduced in green house growing at the Núcleo de Estações Experimentais of the Universidade Estadual do Oeste do Paraná, Marechal Cândido Rondon Campus. The experimental design was made in randomized block design in a factorial schema 4 x 2 x 2, with four replications. The first factor "Resistance Inductors" was constituted by ASM, MOS, B. cereus inductors and water (control). The second factor "Pathogen" was constituted by the presence or absence of B. sorokiniana pathogen. The third factor "PGPR" was made up by the presence or absence of the PGPR A. brasilense. The seeds were inoculated with A. brasilense 24 h before sowing. The treatment with the resistance inductors was done 25 days after the plant emergency and 24 h after it, the inoculation with the pathogen was done. Evaluations for the quantification of peroxidase enzyme, phenylalanine ammonia-lyase and β-1.3-glucanase enzymes activities were done at 0 h, 24 h, 48 h, 72 h and 96 h after treatment. Gas exchanges were evaluated at 0 h, 24 h, 48 h, 72 h, 96 h and 120 h after treatment. The quantification of diazotrophic was made in the implementation of the experiment, at the moment of the use of the resistance inductors and in the flowering. At the flowering, biometric evaluations were performed, and at the end of the cycle, production analysis were held. The use of resistance inductors was efficient in the control of spot blotch wheat disease. The treatment with inductors did not show any interference on the endophytic diazotrophic microrganism. Higher activity of peroxidases for the MOS treatment was observed, that presented high efficiency on the control of the disease. No relation between the activities of phenylalanine ammonia lyase and β-1.3-glucanase and the control of spot blotch was observed. A higher tax of liquid assimilation of CO2 (A) in the absence of the pathogen and presence of the A. brasilense was observed, however, MOS reduced the “A”. The internal concentration of CO2 and the leaf transpiration showed as superior in the treatment with the absence of the pathogen. The stomatal conduce was affected by MOS treatment. The length of the flag leaf and leaf area were affected by ASM use. But, the total weight of grain did not suffer interference of the treatments, in spite of the weight of 100 grains to have been superior to ASM.